Sensitive Health Topics With Underserved Patient Populations: Methodological Considerations for Online Focus Group Discussions. (August 2018) - Reisner, Sari L.; Randazzo, Renee K.; White Hughto, Jaclyn M.; Peitzmeier, Sarah; DuBois, L. Zachary; Pardee, Dana J.; Marrow, Elliot; McLean, Sarah; Potter, Jennifer
Online focus group discussions provide an anonymous environment to assess sensitive, health-related experiences that may be difficult to discuss utilizing traditional face-to-face modalities, particularly for marginalized populations such as female-to-male trans masculine (TM) transgender individuals. This article reviews the history, advantages, and disadvantages of online focus groups, with an emphasis for research about sensitive issues with stigmatized, rare, and/or geographically dispersed patient populations. The article then evaluates the success of online focus group discussions as a case study using data from four asynchronous online focus groups conducted between September 2015 and February 2016 that explored topics related to sexual health care access with U.S. TM adults ( N = 29). The rationale for selecting an asynchronous online methodology is described along with the unique methodological considerations that emerged in developing the study protocol. We conclude by sharing lessons learned, including innovations for maximizing participant engagement and comfort to elicit rich qualitative data.